Critical Success Factors Analysis on ERP Project Implementation of Manufacturing Company in Oceania - Michael Markus; Riri Satria; Christine Cecylia Munthe (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Implementing an ERP (Enterprise Resource System) system is very important nowadays to support business processes in a company. In this research, the Manufacturing company made a new ERP change as a presentation to the parent company of the leading plantation that has acquired it and as an answer to the problems faced by business operations. The research aims to identify CSF (Critical Success Factors) in ERP implementation for the parent organization of the plantation that uses SAP (System Application and Product in Data Processing). CSF analysis in SAP implementation is expected to provide reference factors that influence the success of improvisation for SAP implementation projects, especially for parent organizations. This study uses AHP (Analytical Hierarchy Process) to calculate and determine the priority scale of each CSF factor that affects the success of the implementation project. The variables used are distributed to ERP system users to obtain data using a questionnaire. The results of this study indicate that System Reliability and Flexibility are very influential factors, followed by ERP Fit and Top Management Support